2022
DOI: 10.1007/s40618-022-01820-8
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 lockdown negatively impacted on adherence to denosumab therapy: incidence of non-traumatic fractures and role of telemedicine

Abstract: Purpose Coronavirus disease (COVID-19) lockdowns have impacted on management of osteoporosis and the use of telemedicine is increasingly widespread albeit supported by little evidence so far. The aim of the study is to assess adherence to denosumab and incidence of non-traumatic fractures during the lockdown compared to the pre-COVID-19 year and to explore the effectiveness of telemedicine in the management of osteoporotic patients. Methods Retrospective, longitudinal, single-center study on patients receiving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…The study of Kahn et al [18] on US national Veterans Affairs healthcare system found that the proportion of patients with inflammatory bowel disease receiving an infusion within 10 weeks of the prior infusion to infusible biologic (infliximab, inflectra, renflexis, and vedolizumab) decreased from 84.6% in 2019 to 73.6% in 2020 (p < 0.0001), with a persistent drop in the weekly number of infusions since late March 2020. De Vincentis et al [19] assessed adherence to denosumab (as a single 60 mg subcutaneous injection every 6 months) in a cohort of Italian osteoporotic patients, showing a reduction from 96,7% in the pre-COVID-19 period to 87.0% during the lockdown (p < 0.0001). They also reported that the majority of patients who were non-adherent and/or discontinued denosumab during the COVID-19 lockdown returned for regular follow-up once pandemic restrictions ceased and that the main reason of non-adherence was that patients were afraid of coming to the hospital due to the COVID-19 contagion risk.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of Kahn et al [18] on US national Veterans Affairs healthcare system found that the proportion of patients with inflammatory bowel disease receiving an infusion within 10 weeks of the prior infusion to infusible biologic (infliximab, inflectra, renflexis, and vedolizumab) decreased from 84.6% in 2019 to 73.6% in 2020 (p < 0.0001), with a persistent drop in the weekly number of infusions since late March 2020. De Vincentis et al [19] assessed adherence to denosumab (as a single 60 mg subcutaneous injection every 6 months) in a cohort of Italian osteoporotic patients, showing a reduction from 96,7% in the pre-COVID-19 period to 87.0% during the lockdown (p < 0.0001). They also reported that the majority of patients who were non-adherent and/or discontinued denosumab during the COVID-19 lockdown returned for regular follow-up once pandemic restrictions ceased and that the main reason of non-adherence was that patients were afraid of coming to the hospital due to the COVID-19 contagion risk.…”
Section: Resultsmentioning
confidence: 99%
“…The coronavirus disease 2019 (COVID- 19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has posed major challenges to healthcare systems, mainly during the years 2020 and 2021. Although many countries are currently going through a transitional period, in which health systems are, at different rates, returning to pre-pandemic levels, the effects of COVID-19 pandemic were initially extremely impactful.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the pandemic of Coronavirus disease 19 (COVID-19) has brought some impact on the management of osteoporosis [56][57][58]. For example, the prevalence of non-adherence of denosumab was higher during the COVID-19 lockdown than before [56]. Since medicine persistence is one of the key drivers of cost effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the difficulties in disease management should be kept into account, during a period of recurring lockdowns when patients have been mostly managed via telemedicine, being this last modality characterized by both advantages and weak points. In fact, some studies have also demonstrated an overall lower treatment adherence during pandemic closures, although the application of remote selection criteria for face-to-face visits (i.e., triage by phone) has been proven to be useful in scheduling a more precise follow-up [ 10 , 11 ]. In addition, we aimed to verify if and how much the infection course was influenced by the typical complications of AC and CD (i.e., hypertension and metabolic issues).…”
Section: Introductionmentioning
confidence: 99%